THE IMPACT OF ANGER MANAGEMENT TRAINING ON ANGER, AGGRESSION AND PROBLEM SOLVING SKILLS OF PRIMARY SCHOOL STUDENTS - Nergüz Bulut Serin (Informascope, 2019)
The purpose of this study was to determine the effect of the group anger management training program on the anger, aggression and problem solving skills of adolescents. The research is a semi-experimental study based on pre-test-post-test model with control group. The study consisted of a total of 36 students, 18 of which were in the experimental group and 18 of which were in the control group. "Anger Inventory for Children", "Aggression Scale" and "Problem Solving Inventory for Children" were used as data collection tools. In terms of the data analysis, the suitability of the data for normal distributions was determined by the one-sample Kolmogorov-Simirnov test, "t-test" was used for the significance of the difference between the score points of the groups and  As a result of the research, the students learnt the appropriate expression methods by better understanding the concept of anger. It has been observed that the cognitive-behavioural approach used in the implemented curriculum reduces the anger and aggressive behaviours in favour of male students.